The effect of increasing dietary methionine on performance of the early-weaned pig - Owen, K.Q.; Kats, L.J.; Friesen, K.G.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 216 pigs (initially 10.8 lb and 21 d of age) was used in a 35 d growth trial to determine the effect of increased dietary methionine on growth performance for the early-weaned pig when offered a porcine plasma-based diet. During d 0 to 21 postweaning, increasing methionine levels were obtained by adding DL-methionine to a common basal diet. The control diet was corn-soybean meal-based; contained 10% spray-dried porcine plasma (SDPP), 20% dried whey, 3% lactose, and 1.75% spray-dried blood meal (SDBM); and was formulated to contain 1.6% lysine and .28% methionine. DL-methionine replaced sucrose in the control diet to achieve the experimental dietary methionine levels of .28, .32, .36, .40, .44, and .48%. Six pigs were housed per pen with six pens per treatment. From d 21 to 35 postweaning, all pigs were switched to a common diet containing 10% dried whey and 2.5% SDBM and formulated to contain 1.25% lysine. During d 0 to 21, average daily gain (ADG), average daily feed intake (ADFI), and feed efficiency (F/G) were improved quadratically as dietary methionine increased, with maximum growth performance being obtained between .40 and .44% dietary methionine. Average daily gain was not affected during the second half (d 21 to 35) of the trial. However, both ADFI and feed efficiency were improved with increasing methionine level fed during phase I. On d 7 and 14 postweaning, blood urea N was reduced as dietary methionine increased. Pigs fed .40% dietary methionine had the lowest blood urea N concentration on d 14 compared to pigs fed the other methionine levels. Cumulative (d 0 to 35) ADG and ADFI were maximized between .40 and .44% dietary methionine. These data suggest that the early-weaned pig requires approximately .40 to .44% dietary methionine to optimize growth performance. This corresponds to .345 to .385% digestible methionine and 1.27 and 1.55 g/d of methionine intake from d 0 to 14 postweaning. These requirements are substantially higher than those previously recommended.
Keywords: Swine; Methionine; Starter pigs; Performance